Bacterial biosurfactants, and their role in microbial enhanced oil recovery (MEOR) - Khire, Jayant Malhar (Biosurfactants, 2010)
Surfactants are chemically synthesized surface-active compounds widely used for large number of applications in various industries. During last few years there is increase demand of biological surface-active compounds or biosurfactants which are produced by large number of microorganisms as they exert biodegradability, low toxicity and widespread application compared to chemical surfactants. They can be used as emulsifiers, de-emulsifiers, wetting agents, spreading agents, foaming agents, functional food ingredients and detergents. Various experiments at laboratory scale on sand-pack columns and field trials have successfully indicated effectiveness of biosurfactants in microbial enhanced oil recovery (MEOR).